Treatment of domestic wastewater by an integrated anaerobic fluidized-bed membrane bioreactor under moderate to low temperature conditions - Gao, Da-Wen; Hu, Qi; Yao, Chen; Ren, Nan-Qi (Bioresource technology, 2014)
•The accumulation of VFAs was affected by temperature significantly.•Low temperature accelerated membrane fouling process.•Proteins were the dominant EPSs causing membrane fouling at low temperature.•Granular active carbon can mitigate membrane fouling via protein absorption. The performance of a novel integrated anaerobic fluidized-bed membrane bioreactor (IAFMBR) for treating practical domestic wastewater was investigated at a step dropped temperature from 35, 25, to 15°C. The COD removal was 74.0±3.7%, 67.1±2.9% and 51.1±2.6% at 35, 25 and 15°C, respectively. The COD removal depended both on influent strength and operational temperature. The accumulation of VFAs (Volatile Fatty Acids) was affected by temperature, and acetic acid was the most sensitive one to the decrease of temperature. The methanogenic activity of the sludge decreased eventually and the methane yield was dropped from 0.17±0.03, 0.15±0.02 to 0.10±0.01L/Ld. And as compared with a mesophilic temperature, a low temperature can accelerate membrane biofouling. Proteins were the dominant matters causing membrane fouling at low temperature and membrane fouling can be mitigated by granular active carbon (GAC) through protein absorption.